Network Building in Practice – the System of Practical Training at Kaposvár University Faculty of Pedagogy - Bencéné Fekete, Andrea; Horváthné Tóth, Ildikó (Acta Scientiarum Socialium, 2015)
Network Building in Practice – the System of Practical Training at Kaposvár University Faculty of Pedagogy Learning is good. Learning together is even better because personal connections, mutual talks, exchanging experience, openness, flexibility and confidence in each other mean successful learning in teams. The study presents the practice network, the cooperation model between the outer practice places, partner institutions and mentors’ joint work of teacher training and other trainings closely connected to the field of teacher training at the Faculty of Pedagogy of Kaposvár University. We give a short presentation about the bases of network theory, the realization of learning in a network, the shaping of innovation systems focusing mainly on teaching networks, then on the good practice taking shape during building networks and we also throw light on the results of our cooperation partners’ joint dissemination of knowledge.
Keywords: network; training; practice; organizations